Digital Map Media: The Needs of Digital Media for Social Studies Learning in Grade IV Elementary School - Rahmawati, Dian Nur; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra; Zainuddin, Mohammad (Universitas Pendidikan Ganesha, 2024)
The development of digital map learning media in social studies learning in elementary schools has several urgencies that need to be considered, especially in the context of developments in information technology and modern educational needs. This research aims to analyze the needs for developing digital map learning media in elementary school social studies learning. This research uses qualitative and quantitative research designs. Participants in this research were teachers and students. The sample in this research was 1 teacher and 11 students at elementary school. Data collection techniques included interviews, questionnaires and observations. Research findings from interviews with teachers show that teachers know about digital maps but only limited to Google Maps and Google Earth. The teacher explained that digital maps are suitable to be developed to facilitate understanding of Hindu Buddhist Kingdom material by paying attention to an attractive appearance, short and clear content, and combining it with technology. Research findings from the results of student questionnaires show that 90% of students are interested in learning material about the Hindu Buddhist Kingdom using digital maps. Thus, the results of the analysis of teacher and student needs show that digital map media is needed by students. This research can be developed to develop digital map media based on Hindu Buddhist Kingdom material as a social study learning medium for fourth grade elementary school students.